2006 European Microwave Conference 2006
DOI: 10.1109/eumc.2006.281412
|View full text |Cite
|
Sign up to set email alerts
|

Phase Center Stable Ultra Wide-Band Antenna for EMC Field Sensing

Abstract: Abstract-Leaky lens antennas are linearly polarized directive antennas constituted by long slots etched on a ground plane that separates a dense dielectric, shaped to form a lens, from free space. These antennas are characterized by significant directivity, very low dispersion and they are suited to be integrated with the receive modules. These properties arise from the particular leaky wave radiation mechanism that these antennas exploit. In this contribution, the ultra-wide band version of the antenna descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In the aforementioned work, it was shown that the main beam remains at a virtually fixed angle in both the E and H-planes over a frequency range from 13 to 17 GHz. An even more broadband variant of this antenna, the "pyramid antenna" was presented by the same authors in [7], where it was shown that the antenna operates over a decade bandwidth, from 4 to 40 GHz. One drawback of the broadband LWAs of [7] and [8] is the fact that they are inherently three-dimensional structures consisting of large dielectric lenses mounted on top of a ground plane, and therefore do not exhibit a low profile.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the aforementioned work, it was shown that the main beam remains at a virtually fixed angle in both the E and H-planes over a frequency range from 13 to 17 GHz. An even more broadband variant of this antenna, the "pyramid antenna" was presented by the same authors in [7], where it was shown that the antenna operates over a decade bandwidth, from 4 to 40 GHz. One drawback of the broadband LWAs of [7] and [8] is the fact that they are inherently three-dimensional structures consisting of large dielectric lenses mounted on top of a ground plane, and therefore do not exhibit a low profile.…”
Section: Introductionmentioning
confidence: 97%
“…Some of these applications include wireless local area networks (WLAN), ultrawideband (UWB) technology, satellite communications, electromagnetic compatibility (EMC) testing and radiometric field sensing [7]. Such a wideband leaky-wave antenna was recently presented by Neto et al in [8], and consisted of a tapered elliptical dielectric lens mounted on top of a slot etched in a ground plane.…”
Section: Introductionmentioning
confidence: 99%